Comparative study between percutaneous pinning and ligamentotaxis using external fixator in the management of distal end radius fracture in adults: a prospective study - D. K., Sridhar; S., Raghavendra T.; Mahida, Jaipalsinh R. (International Journal of Research in Orthopaedics, 2017)
Background: Fractures of distal end of radius are beginning at the proximal end of pronator quadratus and ending at the radio-carpal articulation. The final aim in the management of comminuted intra-articular fractures of distal radius is to restore normal function. Recognition of patterns that are inherently unstable and therefore necessitate additional forms of fixation to secure and maintain reduction and prevent late collapse is the key for successful management of the more complex fractures of distal radius. The aim is to study the functional outcome of surgical management of comminuted intra-articular fractures of distal end radius by comparing 2 different methods of surgical interventions. Methods: In study of 30 cases treated in period from March 2008 to September 2009 at St. Martha’s Hospital by ligamentotaxis and percutaneous pinning, all patients with compound fractures, Frykman’s IV, V, VI, VII and VIII, comminuted fractures and in fractures where reduction was lost following closed reduction and POP application were taken into consideration. Results: The average age in males were 41.35 years and female were 35 years. 12 (40%) fractures were type VII, 6 (20%) were type VIII, 9 (30%) were type IV and 3 cases (10%) was type V. functional results in ligamentotaxis group (G1) 7 cases had excellent results (47%), in percutaneous pinning (G2), 3 cases had excellent result (20%). In ligamentotaxis group (G1) 3 had good results (20%), in percutaneous group (G2) 6 had good results (40%). In ligamentotaxis group (G1) 5 had poor results (33%), in percutaneous pinning group (G2) 6 had poor results (40%). Conclusions: In comparative studies, external fixation with percutaneous pinning consistently achieves better anatomical results as compared to percutaneous pinning alone. In our study, also this technique has shown satisfactory result that lead to high rate of return to pre-injury status, high level of patient satisfaction and low rate of complications.